Ефективність застосування ентеросорбенту „Карболайн” при лікуванні хворих на хронічне обструктивне захворювання легень = Effectiveness of the usage of chelator „Karbolayn” in treating patients with chronic obstructive pulmonary disease - Andreychyn, S. M.; Lototska, S. V. (Journal of Education, Health and Sport, 2015)
Andreychyn S M, Lototska S V. Ефективність застосування ентеросорбенту „Карболайн” при лікуванні хворих на хронічне обструктивне захворювання легень = Effectiveness of the usage of chelator „Karbolayn” in treating patients with chronic obstructive pulmonary disease. Journal of Education, Health and Sport. 2015;5(5):125-130. ISSN 2391-8306. DOI 10.5281/zenodo.17463 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A125-130 https://pbn.nauka.gov.pl/works/559202 http://dx.doi.org/10.5281/zenodo.17463 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. УДК 616.233-002-036.12-085.246.2:546.26 ЕФЕКТИВНІСТЬ ЗАСТОСУВАННЯ ЕНТЕРОСОРБЕНТУ „КАРБОЛАЙН” ПРИ ЛІКУВАННІ ХВОРИХ НА ХРОНІЧНЕ ОБСТРУКТИВНЕ ЗАХВОРЮВАННЯ ЛЕГЕНЬ EFFECTIVENESS OF THE USAGE OF CHELATOR „KARBOLAYN” IN TREATING PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE С. М. Андрейчин, С. В. Лотоцька S M Andreychyn, S V Lototska ДВНЗ «Тернопільський державний медичний університет iм. І. Я. Горбачевського МОЗ України» SHEI "I.Ya. Horbachevsky Ternopil State Medical University of MPH of Ukraine" Summary: The results of the study of parameters of endogenous intoxication syndrome in patients with COPD before and after treatment. The results have shown that the disease is accompanied by severe endotoxemia, which manifests in increasing content of middle mass molecules and erythrocyte index of intoxication in serum. The positive impact of carbon enterosorbent "Karbolayn" was noted in the treatment of these patients - the evidence was the reduction of middle mass molecules and normalization of erythrocyte index of intoxication. Key words: COPD, karbolayn, syndrome of endogenous intoxication. Резюме. Наведено результати дослідження показників синдрому ендогенної інтоксикації у хворих на ХОЗЛ до та після лікування. Отримані результати показали, що захворювання супроводжується вираженим ендотоксикозом, який проявляється збільшенням вмісту молекул середньої маси та еритроцитарного індексу інтоксикацйії в сироватці крові. Відзначено позитивний вплив вуглецевого ентеросорбенту «Карболайн» в комплексному лікуванні таких хворих, про що свідчать зменшення рівня молекул середньої маси та нормалізація еритроцитарного індексу інтоксикації. Ключові слова: ХОЗЛ, карболайн, синдром ендогенної інтоксикації.